Biodiversity of free-living ciliates of the Kura River basin (within Azerbaijan) - Alekperov, Ilham Kh.; Tahirova, Elyana N. (Experimental Biology and Biotechnology, 2020)
As a result of long therm free-living ciliates investigation of the Kura River basin, in all 308 species have been noted. The article provides information on the ciliates species diversity of 8 sample points, across the Kura River within Azerbaijan – from Georgian state border to the delta. The freshwater ciliates species diversity varies considerably depending on location and environment sample points. The greatest diversity of freshwater ciliates noted in Mingechevir and Varvara reservoirs (128 and 140 species respectively), which in our opinion, is related with a variety of biotopes in these reservoirs and an abundance of food organisms. The analysis on the occurrence of ciliates showed that the group of dominants (noted in more than 80 % of all samples) includes 10.71 % of the total species diversity, and the group of regular ones (occurrence less than 80, but more than 50 %) 13.60 % of the entire species composition, 71.47 % belong to the largest group of irregular ones (occurrence from 30 to 50 % in samples), and 4.22 % of the total species diversity to the group of random species (occurrence less than 30 % of all samples). It has been established that the largest group of irregular species is consist ciliates, confined to a certain time of the year – mainly in spring and fall. At the same time, part of this group species appeared in the communities only in the summer.
Keywords: ciliates; species diversity; Kura River basin; Azerbaijan